2013
DOI: 10.1002/2012wr012795
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the successive V6 and V7 TRMM multisatellite precipitation analysis over the Continental United States

Abstract: The spatial error structure of surface precipitation derived from successive versions of the TRMM Multisatellite Precipitation Analysis (TMPA) algorithms are systematically studied through comparison with the Climate Prediction Center Unified Gauge daily precipitation Analysis (CPCUGA) over the Continental United States (CONUS) for 3 years from June 2008 to May 2011. The TMPA products include the version‐6(V6) and version‐7(V7) real‐time products 3B42RT (3B42RTV6 and 3B42RTV7) and research products 3B42 (3B42V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
105
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 32 publications
11
105
0
1
Order By: Relevance
“…The worse agreements between the two datasets (TMPA and gauge-based) were found in monsoon season on both pixel and basin scales. Recently, Anjum et al [15], Chen et al [16], and Derin et al [20] have also reported significant over and underestimations of observed seasonal precipitation by real and post real time TMPA products in different regions of the world.…”
Section: Evaluation Of Tmpa Products At Different Spatial and Temporamentioning
confidence: 99%
See 1 more Smart Citation
“…The worse agreements between the two datasets (TMPA and gauge-based) were found in monsoon season on both pixel and basin scales. Recently, Anjum et al [15], Chen et al [16], and Derin et al [20] have also reported significant over and underestimations of observed seasonal precipitation by real and post real time TMPA products in different regions of the world.…”
Section: Evaluation Of Tmpa Products At Different Spatial and Temporamentioning
confidence: 99%
“…A large number of studies have evaluated the performance of 3V42V6 in many parts of world [11][12][13][14][15]. Although some studies have also documented the performance of 3B42V7 in different regions of the world [14][15][16][17][18], limited studies have reported on its performance relative to its predecessor (3B42V6) and near real time product (3B42RT) in complex terrain regions having cryospheric environment. Thus, a river basin situated in the high mountains of Hindukush-Karakoram-Himalayan (HKH) region [15,19] has been chosen for undertaking a comprehensive and comparative assessment of TMPA products with a wide variety of statistical indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these two quasi-global satellite precipitation products have been widely utilized in various hydrological and meteorological applications in China [7][8][9][10][11][12][13]. Over the years, there have been many efforts to compare and validate available satellite precipitation estimates at global, regional, or basin scales [9,10,[14][15][16][17][18][19][20][21][22][23][24][25]. An essential point when trying to evaluate the data accuracy is to know where the retrieval errors are coming from.…”
Section: Introductionmentioning
confidence: 99%
“…Each precipitation field is best interpreted as the precipitation rate effective at the nominal observation time (Huffman, et al, 2007 (Chen, et al, 2013). And the IR data are from National Climatic Data Center (NCDC) and Climate Prediction Center (CPC), which are calibrated by the Microwave data according to the algorithm.…”
Section: Trmm 3b42v7 Datamentioning
confidence: 99%